The role of America in the development trend of Iranian nuclear program - Hasan Ali Bayli, Hasan Fadaei Shojaei, (Opción, 2019)
The aim of the study is to investigate the role of America in the development trend of Iranian nuclear program before and after the Islamic revolution via comparative qualitative research methods. As a result, after passing 3 decades from the 1979 Revolution, many Iranians in particular the youth have lost their interest in the Islamic Revolution, however the nuclear program of their country is still a source of pride for them. In conclusion, America which undertakes the leadership of western countries on the nuclear issue of Iran should continue the direct negotiation with Iran to solve the Iranian nuclear issue.